The Nonlinear and Gender-Related Relationships of Face Attractiveness and Typicality With Perceived Trustworthiness - Li, Nan; Liu, Ning (Frontiers in Psychology, 2021)
Perceived trustworthiness is one of the most important facial traits in social interaction. To elucidate how facial trustworthiness is assessed by others and its relationship to other facial traits would have significant theoretical and practical implications. Prior studies have shown that perceived attractiveness and typicality of a face may contribute to trustworthiness judgments, i.e., trustworthy faces are always the typical and attractive ones. Here, by conducting judgments of facial traits (i.e., trustworthiness, attractiveness, and typicality) on the same set of faces, we revealed a more profound relationship among these facial traits. First, we found that trustworthiness judgments did not always peak at the average face, in contrast to previous research. Second, trustworthiness exhibited a nonlinear relationship with attractiveness and typicality: men relied more on typicality when judging a face as untrustworthy or neutral, whereas women relied more on typicality when judging a face as untrustworthy but more on attractiveness when judging a face as trustworthy. Third, women and men may utilize different traits to evaluate face trustworthiness: The relationship between trustworthiness and typicality judgments were closer in men than in women, whereas women counted on face attractiveness more than men did to evaluate face trustworthiness. These findings demonstrate that judging the trustworthiness of a face is a more complex process than previously thought, which may lead to a better understanding of the mechanisms underlying highly flexible and sophisticated social interactions in humans.